Cultural Values and Ecosystem Management at the Subwatershed Level. (21st July 2014) - Retallack, Matthew; Schott, Stephan
ABSTRACT The valuation of ecosystem services is often centred on the proper integration of ecological and economic values but overlooks the social and cultural dimensions of ecosystem changes. We argue that these factors are essential for sustainable outcomes because they underlie preference formation, affect ownership over decision making and may help ensure that primary non‐market services needed to maintain ecosystem functions are sustained. In this study, we propose a conceptual framework for ecosystem service valuation at a local subwatershed scale that employs participatory democracy and discourse‐based methods to elicit and develop value systems while at the same time serving as a decision‐making process. Incorporating cultural theory and perceptions of risk tolerance, the framework discusses the importance of cultural considerations to achieving intergenerational equity, a precondition for sustainable development. The framework is applied to the case of Chelsea, Québec (Canada), and used to examine the community consultation component of a policy development process. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment